MADS-box gene AaSEP4 promotes artemisinin biosynthesis in Artemisia annua - Chen, Tian-Tian; Yao, Xing-Hao; Liu, Hang; Li, Yong-Peng; Qin, Wei; Yan, Xin; Wang, Xiu-Yun; Peng, Bo-Wen; Zhang, Yao-Jie; Shao, Jin; Hu, Xin-Yi; Miao, Qing; et al. (Frontiers in Plant Science, 2022)
The plant Artemisia annua is well known for its production of artemisinin, a sesquiterpene lactone that is an effective antimalarial compound. Although remarkable progress has been made towards understanding artemisinin biosynthesis, the effect of MADS-box family transcription factors on artemisinin biosynthesis is still poorly understood. In this study, we identified a MADS transcription factor, AaSEP4, that was predominantly expressed in trichome. AaSEP4 acts as a nuclear-localized transcriptional activator activating the expression of AaGSW1 (GLANDULAR TRICHOME-SPECIFIC WRKY1). Dual-luciferase and Yeast one hybrid assays revealed that AaSEP4 directly bound to the CArG motif in the promoter region of AaGSW1. Overexpression of AaSEP4 in A. annua significantly induced the expression of AaGSW1 and four artemisinin biosynthesis genes, including amorpha-4,11-diene synthase (ADS), cytochrome P450 monooxygenase (CYP71AV1), double-bond reductase 2 (DBR2) and aldehyde dehydrogenase 1 (ALDH1). Furthermore, the results of high-performance liquid chromatography (HPLC) showed that the artemisinin content was significantly increased in the AaSEP4 overexpression plants. In addition, RT-qPCR results showed that AaSEP4 was induced by methyl jasmonic acid (MeJA) treatment. Taken together, these results explicitly demonstrate that AaSEP4 is a positive regulator of artemisinin biosynthesis, which can be used in the development of high-artemisinin yielding A. annua varieties.